2019
DOI: 10.1108/ijppm-12-2018-0425
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable supply chain performance, its practice and impact on barriers to collaboration

Abstract: Purpose Sustainable supply chain (SSC) provides one opportunity to achieve competitive advantage. To achieve SSC through triple bottom line (TBL) – economic, environment and social – is extensively discussed. Most literature in dealing with environmental issues undermine social dimension even though its potential to bring outstanding results by earning customers loyalty and commitment is immense. Local orientation and different context motivate firms to prioritize sustainability dimensions differently. The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 64 publications
0
36
0
1
Order By: Relevance
“…To test the hypotheses, the conceptual model depicted in Figure 1 was tested using the following fit indices: chi-squared test, normed fit index (NFI), comparative fit index (CFI), incremental fit index (IFI), goodness-of-fit index (GFI) and root mean square error of approximation (RMSEA). For a suitable fit, the ratio of chi-square values to freedom degrees should be less than 3.0 (Anuj et al, 2018), and the NFI, CFI, IFI and GFI values should be greater than 0.9 (Kumar and Goswami, 2019), and the RMSEA should be less than 0.05 (Zaheer and Trkman, 2017). The ratio of chi-square 5 287.21 to df 5 146 was 1.97.…”
Section: Model Fit Assessmentmentioning
confidence: 99%
“…To test the hypotheses, the conceptual model depicted in Figure 1 was tested using the following fit indices: chi-squared test, normed fit index (NFI), comparative fit index (CFI), incremental fit index (IFI), goodness-of-fit index (GFI) and root mean square error of approximation (RMSEA). For a suitable fit, the ratio of chi-square values to freedom degrees should be less than 3.0 (Anuj et al, 2018), and the NFI, CFI, IFI and GFI values should be greater than 0.9 (Kumar and Goswami, 2019), and the RMSEA should be less than 0.05 (Zaheer and Trkman, 2017). The ratio of chi-square 5 287.21 to df 5 146 was 1.97.…”
Section: Model Fit Assessmentmentioning
confidence: 99%
“…SCC seems more sensitive to relational bonding and preparedness together, future research on relational bonding and preparedness should confirm the same. This study does not consider sustainability elements from environmental and social dimensions (Ferro et al, 2019;Kumar and Goswami, 2019). Future research can extend the proposed SCC framework by including the sustainability elements.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…The study also found that collaboration is positively related to environmental performance. Collaboration is considered a key mechanism through with sustainability is achieved (Blome et al, 2014;Kumar & Mohit, 2019;Pakdeechoho & Vatcharapol, 2018). Several studies have found a positive impact of collaboration with suppliers on environmental sustainability (e.g.…”
Section: Discussionmentioning
confidence: 99%